Association of Abdominal Obesity and Diabetes among the Adult Tribal Population in Tamil Nadu - Kalaivanan Ramamoorthy; Logaraj Muthunarayanan; M Palanivel Sundaram; M Devivaraprasad; VV Anantharaman (Wolters Kluwer Medknow Publications, 2024)
Background: Previously overweight and obesity are considered to be an issue of high-income countries but now increasingly becoming more prevalent in low-income and middle-income countries. Obesity and overweight are growing health issues in India. It is important to determine the quantum of the risk contribution by individual risk factor siuch as abdominal obesity. Aims: To find out the association of abdominal obesity and diabetes among the adult tribal population. Methods and Material: A cross-sectional study was conducted using multi-stage random sampling techniques. Using a pretested validated modified Stepwise questionnaire, a detailed interview with the participants aged above 30 years were performed. Random blood sugar and anthropometric parameters were estimated for all the participants. Chi-square test and multivariate regression analysis were used to study association. Results: Prevalence of abdominal obesity was 49.6% [211] among the study participants. Prevalence of diabetes was 7.8% [33] among the study population and 92.2% [392] of them were nondiabetic. Normal WHR was seen among 27.3% [9] of the diabetic individuals. High WHR was seen among 72.7% [24] of diabetic individuals. Gender, Illiterate, BMI, and waist-hip ratio shows significant association with diabetes. Conclusions: The prevalence of abdominal obesity was higher in the study population. As this burden among tribal people is on the increasing trend when compared with other general populations, effective strategies to prevent this have to be devised among the tribal population.